Advanced approach for simulation results saving from discrete element method. (October 2019) - Dranishnykov, Serhii; Dosta, Maksym
Highlights: A novel approach for saving simulation results obtained from DEM is proposed. The combination of lossy and lossless methods is applied for data compression. The efficiency of the proposed method is investigated in the case studies selected considering the classification of problems solved with DEM. Abstract: An advanced approach for saving of simulation results obtained from modelling of granular materials with the discrete element method (DEM) is developed. In order to reduce the volume of generated data, a combination of lossy and lossless compression methods is proposed. This combination allows one to compress simulation results with predefined numerical tolerances. The top-down time-ratio compression algorithm and DEFLATE compression method are used as lossy and lossless methods accordingly. The developed method has been implemented with the C++ programming language and integrated as a subsystem for data storage into DEM simulation framework MUSEN. To estimate the efficiency of the contributed saving approach, several simulation case studies have been selected and analysed. The obtained results have shown that the application of the proposed method makes it possible to reduce the volume of saved data significantly and to avoid the loss of important information.